Off-label use in adult palliative care – more common than expected. A retrospective chart review. Issue 6 (1st April 2021) - Hagemann, Vera; Bausewein, Claudia; Remi, Constanze
Abstract : Objective: Off-label drug use seems to be integral to adult palliative care pharmacotherapy. Balancing potential risks and benefits in the context of limited therapeutic options is challenging. To provide specific support for clinicians in dealing with off-label use, it is essential to understand off-label use in everyday clinical practice. The aim of this pilot study was to quantify and describe off-label use in an adult palliative care unit. Methods: Retrospective chart review of all adult patients treated on a palliative care unit in October 2017. All data on drug use (eg, indication, dose, route of administration) were extracted and matched with the prescribing information. Identified off-label use was subsequently compared with recommendations in the relevant literature. The main outcome measure was frequency and type of off-label drug use. Results: Some 2352 drug application days and 93 drugs were identified for 28 patients. Of all drugs, 47 (51%) were used off-label at least once. Most off-label uses concerned indication (57%) followed by mode of administration. In drugs highly relevant to palliative care the rate of off-label use was as high as 67%. The extent to which off-label therapy was supported by literature was very variable and ranged from 0% to 88%. Conclusions: These data from a single unit confirm the high prevalence of off-label use in palliative medicine and demonstrate that off-label use in adult palliative care is multifaceted. The data presented allow for a more precise characterisation of various aspects of off-label use in order to derive concrete further measures for research and clinical practice.